FORMULASI NUTRISI ENTERAL BERBASIS TEPUNG EDAMAME UNTUK ALTERNATIF DIET CAIR PASIEN STROKE - Leiyla Elvizahro; Aprillia Dewi Arum Nur Purwandari; Riska Yunida Prastiwi; Syari Ernawati Putri; Vivi Meiliza Majid (Rumah Sakit Akademik Universitas Gadjah Mada, 2021)
Background: At UGM Academic Hospital, the liquid diet that has been given to stroke patients is a high-energy, high-protein and low-sodium enteral commercial formula. Commercial enteral formula has a relatively expensive price so we need a ready-made enteral product at a more affordable price. Hospitals can utilize potential ingredients to produce ready-to-use enteral formulas, one of which is edamame bean flour. Objective: Producing edamame flour-based enteral nutrition products that can be organoleptically acceptable, meet nutritional requirements, and meet the physical requirements of enteral nutrition for stroke patients. Design: Laboratory experimental research with a Completely Randomized Design with four research stage: 1) Making and testing the nutritional value of edamame flour, 2) Formulation of edamame flour-based enteral nutrition, 3) Testing of organoleptic quality, physical properties, and nutritional value and calculating the cost of enteral nutrition edamame flour based, 4) Determination of the selected formula. Results: Edamame flour produced in this study had the highest percentage of nutrient content in the form of protein (31.5%) and antioxidant activity of 69.75%. Based on the calculation of nutritional value, determined 3 formulas, namely formula A (comparison of edamame flour: 1: 4 skim milk), formula B (2: 3), and formula C (1: 2). From the results of testing the nutritional value, physical properties, cost, and level of preference, formula A is determined as the chosen formula. Formula A has a protein content of 21.88%; energy content of 332.54 Kcal / 100 g; viscosity 8.6 cP; osmolality 436 mOsmol / Kg water; and most preferred panelists in terms of taste. Conclusions: Edamame flour formula can be used as an alternative liquid diet for stroke patients with energy and protein content such as commercial stroke formulas.